CURRENT STATUS OF ANTHROP ACTIVITIES FROM ROVINARI MINING BASIN - Ramona Violeta MITRAN; Daniela CÎRŢÎNĂ (Fiabilitate şi Durabilitate)
Environmental problems are more and more present due to the increase of polluting phenomena “pollution has no boundaries”, therefore, it is necessary to control and manage the polluting factors generated by the mining activity. Environmental protection efforts through the elaboration of non-polluting technologies, in the field of coal output, are prevented by the considerable financial efforts they imply. The development of the mining activity in the mining perimeters from Rovinari has required solutions for some important problems regarding: establishing the rational limits of the exploitation perimeters; dimensioning quarries steps and analyzing their stability. In 2011, the mining activity in Rovinari mining basin takes place in 8 mining perimeters: Gârla, Tismana I, Tismana II, Rovinari Est, Pinoasa, Roşia – Jiu, Peşteana Sud, Peşteana Nord, which are located in north-west of Rovinari coal-bearing basin related to Rovinari steam power plant